EFFECTIVENESS TEST OF INSULIN (Thitonia diversifolia (Hemsl.) A. Gray) LEAF INFUSION ON DECREASING BLOOD GLUCOSE LEVELS IN MALE WHITE MICE (MUS MUSCULUS) - Andy Brata; Yossie Bella Pratiwi (Poltekkes Kemenkes Jambi, 2019)
Background: Insulin leaf is one of the plants that has the use of its leaves. Insulin leaves contain flavonoids that are thought to reduce blood glucose levels. This study aims to determine the effectiveness of insulin leaf infusion on decreasing blood glucose levels in male white mice. Methods: This study was an experimental study with a Pretest-Posttest with Control Group design. Test animals used were 25 male white mice which were divided into 5 groups, namely the negative control group (Na-CMC), positive control group (Glibenklamid), insulin leaf infusion group 420 mg, 840 mg, and 1260 mg. Observation and checking of blood glucose levels in mice in the 30th, 60th, 90th, and 120th minutes. Results: One-Way ANOVA statistical test results showed significant results in the 90th and 120th minutes. Followed by the Duncan Post Hoc test which showed the best dose, ie a dose of 420 mg which had an effect comparable to Glibenclamide 5 mg, then followed by a dose of 1260 mg and 840 mg which already have antihyperglycemic effects but no difference has been seen. Conclusion: The dose of infusion that can reduce blood glucose levels is a dose of 420 mg with a decrease in maximum blood glucose levels in the 90th minute and 120th minute.